Fuzzy methods and eye gaze for cooperative robot communication. (24th February 2010) - Zhu, Dingyun; Gedeon, Tom; Mendis, B. Sumudu U.
We introduce our fuzzy signature and pattern matching with possibility calculation based approach for modelling the communication between human-control robot and a pair of assistant robots for completing cooperative tasks in a simulated environment. We show that a sophisticated extension using computerised recognition of eye gaze with fuzzy modelling based interpretation of possible intentions effectively eliminates the need of any physical control from the human's side. The experiment results show a good improvement of time saved by the use of our eye gaze intention in the context.